Oxford business English dictionary : for learners of English - Parkinson, Dilys; Noble, Joseph (Oxford : Oxford University Press, 2005)
CD-ROM includes: Everything in the dictionary, plus extra words and examples; pronounciation for listening and practicing; search options for words used in Financy, Marketing, HR, etc.; listening exercises to prepare for the BEC exams; grammar and vocabulary exercises.
EL-Pro
System requirements: Windows ME/2000/XP, 300 MHz processor, 64 Mb RAM, 8 Mb graphics memory.
Friends' Book Corner
Keywords: English language -- Business English -- Dictionaries